The profile of the Utilization of Information and Communication Technology and Its Potency for Blended Learning Development in Biology Education Department of Teacher Training and Education Faculty of UNS - Bowo Sugiharto (Universitas Sebelas Maret, 2015)
The purpose of this research is to describe the profile of the utilization of information and communication technology (ICT) as well as the potential for blended learning development in students of Biology Education Department of Teacher Training and Education Faculty of UNS. The research is descriptive research. The sample used is biology education student consist of students in 2nd, 4th, and 6th semester totaled 90 students on academic year 2014/ 2015 .The survey proportionally was done in March 2015. The data of the research described qualitatively as well as using descriptive statistics. The utilization of information and communication technology on biology education student of is quite high and mostly used for purposes of social networking which is indicated by average of social network account ownership is more than 4 social network accounts. In addition, the frequency of internet access per student are also high that is once a day as many as 35 students (38.89%) more than once/week as much as 9 students (10%), once a week as much as 1 student (1.11%), and the rest with a frequency not necessarily as many as 45 students (50%). The development of blended learning in Biology Education is possible to do. This is supported by the existence of various activities the use of ICT for the purposes of teaching and learning for example for assignments submitting via e-mail, accessing material of the lectures of lecture’s blog or another site suggested by lecturer, accessing the journal research or subject content, discussion through social networking guided by the lecturer. The form of the development of blended learning which most allows is to use the LMS (Learning Management System).Keywords: utilization of ICT, blended learning